Modelos discretos para formação de enxames de gafanhotos - Stefanello, Ana Paula (2025)
In this work, we propose four Coupled Map Lattice models to analyze the process of locust swarms formation. This dynamic system considers time and space as discrete variables, while the population density is a continuous variable. The dynamics of the model is composed by two different stages: the movement stage and the reaction stage. In the first two models, we assume that individuals move by density-dependent diffusion. In the last two models, we assume that solitary locusts move by taxis and gregarious locusts by aggregation, according to a model proposed by Rossato (2019). In the reaction phase, in all the models, we assume that individuals interact according to the classic SI epidemiological model, in which the susceptible ones are the solitary locusts, while the infectious ones correspond to the gregarious individuals. The results obtained, through numerical simulations, show that only the fourth proposed model is capable of generating significant clusters, with high densities of individuals and, therefore, is effective in describing the locusts swarm formation process.